Intermittent pain of the pelvis in a Syrian woman - Schleenvoigt, Benjamin T.; Theis, Bernhard; Wüst, Michaela; Forstner, Christina; Pletz, Mathias W.; Hagel, Stefan (PLOS Neglected Tropical Diseases, 2020)
null